Navigating Financial Landscapes: Evaluating the Interplay between Bank Health, GCG Self-Assessment, and Performance in Global Banking Institutions - Antonius Ary Setyawan; Klemens Mere; Loso Judijanto; Irwan Moridu; Alfiana, Alfiana (Dinasti Publisher, 2024)
This article examines the intricate relationship between bank health, corporate governance practices, and performance within the global banking sector. As financial landscapes evolve, understanding the dynamics among these factors becomes imperative for stakeholders, regulators, and investors alike. The article synthesizes existing literature to elucidate how bank health, as a multifaceted construct, influences corporate governance mechanisms and ultimately impacts performance metrics in global banking institutions. It delves into the significance of effective corporate governance, particularly through self-assessment frameworks such as Good Corporate Governance (GCG), in mitigating risks and enhancing organizational resilience. By employing a systematic literature review methodology, this study identifies key themes, trends, and gaps in current research surrounding the interplay between bank health, GCG self-assessment, and performance. It explores various dimensions including regulatory frameworks, risk management practices, and financial stability indicators to provide a comprehensive understanding of the subject matter. Furthermore, the article offers insights into potential avenues for future research and practical implications for policymakers and industry practitioners. By critically evaluating existing literature, this study contributes to the ongoing discourse on fostering transparency, accountability, and sustainability within the global banking sector. In conclusion, this article serves as a valuable resource for academics, policymakers, and industry professionals seeking to navigate the complex terrain of global financial markets and enhance the resilience and performance of banking institutions in an ever-changing landscape.